(untitled) (Ustozlar uchun, 2026)
Speaking anxiety remains one of the most significant psychological barriers in foreign language learning, particularly in English as a Foreign Language (EFL) contexts. Despite possessing adequate grammatical knowledge, many learners struggle to express themselves orally due to fear of negative evaluation, low self-confidence, and classroom-related stress. This article examines the psychological factors underlying speaking anxiety and their impact on communicative competence. Drawing on sociocultural theory, affective filter hypothesis, and contemporary research on foreign language anxiety, the study analyzes how emotional, cognitive, and social variables influence oral performance. The paper further explores pedagogical strategies for reducing anxiety through scaffolding, supportive classroom environments, task-based interaction, and formative assessment. The findings suggest that addressing psychological dimensions is essential for developing fluency, learner autonomy, and communicative effectiveness in EFL classrooms.